Preparation and characterization of laser-irradiation induced amorphous for GeeSb2Tes phase-change materials - ZHANG Lei HUANG Huan YAN ZhengGuang HAN XlaoDong WANG Yang ZHANG Ze WU YiQun (中国科学：技术科学英文版, 2011)
It has been a challenge to fully understand the structural characteristics of laser-irradiation induced amorphous （L-a） Ge2Sb2Te5 （GST） alloy due to the difficulties of collecting diffraction data from high purity specimens. In this paper, by fabri- cating GST thin films on different substrates, we exhibit an effective way of preparing L-a GST dots in submicron scale on various types of specially designed transmission electron microscope （TEM） grids. The structural characteristics of L-a GST in the form of pair distribution functions （PDF） can be achieved on single dots of L-a GST via selected area electron diffraction （SAED）. This general approach would be convenient for precisely producing laser-irradiation induced materials in submicron scale for structural investigation.